Shortening Dormancy Period of Oil Palm Seeds (Elaeis guineensis) using Sulfuric Acid (H2SO4) and Gibberellic Acid (GA3) Solutions - Yudo Winarso; Bambang Subardjo; Selardi Sastrosayono (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2021)
Soaking oil palm seeds in a solution of sulfuric acid and gibberellic acid is one way to shorten the dormancy period of oil palm seeds. This study aimed to find out the optimum soaking time of oil palm seeds in sulfuric acid solution to accelerate germination, the optimum concentration of gibberellic acid for oil palm seed germination, the interaction between using sulfuric acid and gibberellic acid in accelerating the germination of oil palm seeds and the best treatment combination in all the tried treatments. The experimental design used was a completely randomized design (CRD), with a complete factorial combination with a total of 16 treatments. Each treatment was repeated 4 times, so there were 64 experimental units and each unit was planted with 5 seeds. The results of statistical analysis showed that soaking oil palm seeds in a solution of sulfuric acid and gibberellic acid had an effect on the germination of these seeds. The duration of soaking oil palm seeds for 48 hours in sulfuric acid solution constituted the optimum time for increasing the speed of germination and giving gibberellic acid at a concentration of 300 ppm still accelerated the germination of oil palm seeds and there was no interaction between the length of soaking the seeds in sulfuric acid solution and the concentration of gibberellic acid. Soaking the seeds in a solution of sulfuric acid for 48 hours and gibberellate 300 ppm was the best combination treatment to accelerate the germination of oil palm seeds.